The cumacean genus Iphinoe (Crustacea: Peracarida) from Italian waters and I. daphne n. sp. from the northwestern Adriatic Sea, Mediterranean - Mazziotti, Cristina; Lezzi, Marco (Zootaxa, 2020)
Records of the cumacean genus Iphinoe from Italian coasts are reported with relevant data on the habitat, morphology and geographical distribution of each species. Seven Iphinoe species from the Italian coasts were recorded and are presented here with their own distributional ranges; the description of a new species, Iphinoe daphne n. sp. is also given.                Our results extend the known distribution of some species to new areas of the Mediterranean Sea and suggest that the species Iphinoe adriatica Bâcescu, 1988 can be considered as a nomen dubium, while the presence of I. trispinosa along the Italian coast is doubtful.Finally, a dichotomous key for all Mediterranean Iphinoe species is provided.